A Three Dimensional Kinematic Model of Muckpile Formation in Bench Blasting - Kavetsy A (The Australasian Institute of Mining and Metallurgy, 1988)
In surface mining operations, the ease with which a muckpile may be dug is a dominant factor in mining efficiency. Within broad limits this is largely independent of the fragment size dis- tribution, since the equipment used to move the broken rock is generally larger than in underground mines. In such cases, muck- pile shape and voids ratio within a muckpile heavily influence mine productivity. In a particular operation, the muckpile shape after blasting should be tailored to the digging equipment being used. A front- end loader is best suited to a low, flat-lying, loose muckpile, because of its fairly good mobility and small break-out force with its bucket. In contrast, a rope shovel lacks mobility, generates a much larger break-out force with its bucket, and fills its bucket in a vertical filling motion. Therefore, it is ideally suited to well fragmented, steep faces. In situations where a dragline is used, the requirement for a suitable muckpile depends on the operat- ing scheme of the dragline. For a conventional highwall key method the preferred work- ing level of the dragline is the same as the highwall, so that the dragline may sit over its key. In this situation, the ideal muck- pile shape involves relatively little displacement of the fragmented rock, with a minimal "power trough" at the back of the blast. In throw blasting, on the other hand, it is desirable to cast as much of the spoil as possible across the pit. It is then necessary to optimize the blast design by maximizing the throw percentage under any necessary constraints (e.g. damage, vibration, flyrock, explosive cost).